Investigation on the Rheological Properties of Polydimethylsiloxane - Javanbakht T. (Журнал інженерних наук, 2022)
This paper focuses on studying the rheological properties of polydimethylsiloxane (PDMS). This polymer has been used to fabricate membranes and filters in engineering. The analysis of the rheological properties of this polymer is required for a further investigation of its mechanical behavior. In this study, the rheological behavior of PDMS is reported at different temperatures. This polymer showed steady shear viscosity during a short duration. However, this behavior changed with time and increased more with increasing temperature. The impact of the temperature increase was also observed when the shear viscosity of PDMS increased with shear strain. The increase of torque with shear strain and time was observed at different temperatures. Shear stress increased linearly with the shear rate at 20 °C and 40 °C. As expected, the deformation of the polymer required less shear stress with the increase of temperature. However, the change of shear stress with the shear rate at 60 °C was not linear, and the slope of the curve increased more at high shear rates. The results of this investigation can provide the required information for a better fabrication of membranes and filters with this polymer.